2018
DOI: 10.1371/journal.pone.0209078
|View full text |Cite
|
Sign up to set email alerts
|

Excessive remifentanil during total intravenous anesthesia is associated with increased risk of pain after robotic thyroid surgery

Abstract: The widespread use of remifentanil during total intravenous anesthesia (TIVA) has raised concerns about the risk of postoperative remifentanil-associated pain. Although a recent meta-analysis suggests that remifentanil-associated pain is unlikely to occur in patients with TIVA because of the protective effect of co-administered propofol, the evidence is not conclusive. We retrospectively assessed 635 patients who received robotic thyroid surgery under TIVA to evaluate the risk of remifentanil-associated pain. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…This was supported by another randomized study [ 16 ] whereby intraoperative remifentanil of 0.40 µg/kg/min triggered significant hyperalgesia as well as a higher amount of morphine consumption for 48 h postoperatively when compared to the group that received lower remifentanil dose of 0.05 µg/kg/min. A more recent retrospective study identified that infusion of remifentanil of > 0.2 µg/kg/min increases the probability of treatment-requiring pain for 48 h after robotic thyroid surgery when adjusting for analgesic consumption and its interaction with time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…This was supported by another randomized study [ 16 ] whereby intraoperative remifentanil of 0.40 µg/kg/min triggered significant hyperalgesia as well as a higher amount of morphine consumption for 48 h postoperatively when compared to the group that received lower remifentanil dose of 0.05 µg/kg/min. A more recent retrospective study identified that infusion of remifentanil of > 0.2 µg/kg/min increases the probability of treatment-requiring pain for 48 h after robotic thyroid surgery when adjusting for analgesic consumption and its interaction with time [ 17 ].…”
Section: Discussionmentioning
confidence: 99%